2019
DOI: 10.1177/1039856219889312
|View full text |Cite
|
Sign up to set email alerts
|

Problem gambling among homeless clinic attenders

Abstract: Objective: To examine the relationship between problem gambling and homelessness. Method: A consecutive sample of attenders at psychiatric clinics at three inner-city homeless hostels over 8.5 years. The demographic characteristics, comorbid conditions, pathway and pattern of homelessness of those identified to have problem gambling were compared with those who did not report problem gambling. Results: A total of 2388 individuals were seen at the clinics in the 8 years of the study, of whom 289 (12.1%) reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 10 publications
(12 reference statements)
1
23
0
Order By: Relevance
“…Studies with higher methodological quality provided significantly lower prevalence estimates (13.4% (95% CI 9.0-18.5%)). These results are in line with primary studies focussing on prevalence of PG/GD in the broader context of marginalized housing, which reported prevalence rates of 17% within users of community services in Canada (Lepage et al, 2000), 6% within clients of a Boston-based support program for homeless people with a history of substance abuse (Shaffer et al, 2002) and 12% within patients of mental health services linked to homeless hostels in Sydney (Machart et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Studies with higher methodological quality provided significantly lower prevalence estimates (13.4% (95% CI 9.0-18.5%)). These results are in line with primary studies focussing on prevalence of PG/GD in the broader context of marginalized housing, which reported prevalence rates of 17% within users of community services in Canada (Lepage et al, 2000), 6% within clients of a Boston-based support program for homeless people with a history of substance abuse (Shaffer et al, 2002) and 12% within patients of mental health services linked to homeless hostels in Sydney (Machart et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…First, PG/GD might negatively impact housing stability. It has been frequently reported as a key contributing factor to individuals' pathways into homelessness (Crane et al, 2005;Laere et al, 2009;Machart et al, 2020), at least partially through financial problems and social isolation (Holdsworth & Tiyce, 2013;Sharman & D'Ardenne, 2018). Second, homelessness might reversely be a factor contributing to or at least maintaining PG/GD.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility was assessed for 172 full-text articles, of which 14 nonoverlapping studies met the predefined inclusion criteria (Figure 1). [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Two of these studies were excluded from the quantitative synthesis; a study by André et al, 60 which reported a PBG prevalence of 100% in a sample consisting of only one individual with a psychotic disorder, while a study by Bland et al, 63 which reported a PBG prevalence of 0% in 50 individuals with psychotic disorders, was the only study to use a survey conducted in a general population sample and was therefore excluded due to a distinct methodology as well as a high risk of bias assessment. A sensitivity analysis including these two studies was nevertheless performed.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (41.7%) used the PGSI, four of which used the 8+ threshold for PBG and one used the 3+ threshold for at‐risk gambling, two studies (16.7%) used the NODS, both with the 5+ threshold for PBG, and one study (8.3%) employed the SOGS with the 5+ threshold for PBG. Two studies did not use any validated assessment tool; patients who reported being homeless because of gambling were classified as having PBG in a cross‐sectional study of homeless clinic attendees, 71 while PBG was defined as repeated gambling with disproportionate spending in a retrospective cohort chart review 73 . One study reported a lifetime prevalence of PBG, two studies did not specify any assessment time frame, and all other studies reported current/past‐year prevalences.…”
Section: Resultsmentioning
confidence: 99%
“…Australians have the highest rate of gambling losses per capita in the world. Gambling provides 11% of the state taxation revenue, the largest share of which comes from poker machines 3 . A World Health Organisation (WHO) report 4 on gambling disorder released in 2017 states that the burden of gambling in Australia and New Zealand “is similar to that for major depressive disorder and alcohol misuse and dependence, 2.5 times more than that of diabetes, and 3 times more than drug use disorder”.…”
Section: Introductionmentioning
confidence: 99%